Development and multicentre validation of an agar-based screening method for echinocandin susceptibility testing of Aspergillus species. (18th May 2019) - Meletiadis, Joseph; Siopi, Maria; Kanioura, Lamprini; Jørgensen, Karin Meinike; Perlin, David S; Mouton, Johan W; Arendrup, Maiken Cavling
Abstract: Background: Reference antifungal susceptibility testing of echinocandins against Aspergillus spp. relies on the determination of the minimal effective concentration, which is difficult to perform, time-consuming and subjective. We developed and evaluated in a multicentre study an agar-based screening method for echinocandin susceptibility testing of Aspergillus spp. Methods: Forty WT isolates [10 Aspergillus fumigatus species complex (SC), 10 Aspergillus flavus SC, 10 Aspergillus terreus SC and 10 Aspergillus niger SC] and 4 non-WT A. fumigatus isolates with or without known fks alterations were used. The optimal test conditions and stability over time were evaluated in preliminary studies monitoring colony growth. Twenty-microlitre aliquots of 1–2 McFarland inocula in 0.1% Tween 20 aqueous solution were added to each well and plates were incubated for 24/48 h at 35 ± 2°C. Subsequently, all isolates were tested blindly at three centres using four-well screening plates, containing anidulafungin, caspofungin, micafungin or no antifungal in each of the four wells, respectively. Results: WT isolates produced fluffy colonies on drug-free agar wells only. The non-WT isolates produced fluffy colonies on echinocandin-containing and control agar wells. Using the echinocandin concentrations of 0.25 mg/L anidulafungin, 1 mg/L caspofungin and 0.125 mg/L micafungin, and the compact (non-fluffy) versus fluffy colony morphology endpoint, all centres successfully discriminated non-WT and WT strains even after 24 h. Among the three echinocandins, anidulafungin produced the clearest endpoints. Conclusions: The four-well plate agar method is suitable for echinocandin susceptibility screening of Aspergillus spp. and can be used to detect echinocandin non-WT isolates.